Clinicolaboratory Profile, Treatment, Intensive Care Needs, and Outcome of Pediatric Inflammatory Multisystem Syndrome Temporally Associated with SARS-CoV-2: A Systematic Review and Meta-analysis - Williams, Vijai; Dash, Nabaneeta; Suthar, Renu; Mohandoss, Vichithra; Jaiswal, Nishant; Kavitha, T.K.; Nallasamy, Karthi; Angurana, Suresh Kumar (Journal of Pediatric Intensive Care, 2020)
This study was aimed to summarize the current data on clinicolaboratory features, treatment, intensive care needs, and outcome of pediatric inflammatory multisystem syndrome temporally associated with severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2; PIMS-TS) or multisystem inflammatory syndrome in children (MIS-C). Articles published in PubMed, Web of Science, Scopus, Google Scholar, and novel coronavirus disease 2019 (COVID-19) research database of World Health Organization (WHO), Centers for Disease Control and Prevention (CDC) database, and Cochrane COVID-19 study register between December 1, 2019 and July 10, 2020. Observational studies involving patients <21 years with PIMS-TS or MIS-C were reported the clinicolaboratory features, treatment, intensive care needs, and outcome. The search identified 422 citations and finally 18 studies with 833 participants that were included in this study, and pooled estimate was calculated for parameters of interest utilizing random effect model. The median age was 9 (range: 8–11) years. Fever, gastrointestinal symptoms, rash, conjunctival injection, and respiratory symptoms were common clinical features. Majority (84%) had positive SARS-CoV-2 antibody test and only one-third had positive reverse transcript polymerase chain reaction (RT-PCR). The most common laboratory abnormalities noted were elevated C-reactive protein (CRP), D-dimer, procalcitonin, brain natriuretic peptide (BNP), fibrinogen, ferritin, troponin, interleukin 6 (IL-6), lymphopenia, hypoalbuminemia, and thrombocytopenia. Cardiovascular complications included shock (65%), myocardial dysfunction (61%), myocarditis (65%), and coronary artery abnormalities (39%). Three-fourths of children required admission to pediatric intensive care unit (PICU) where they received vasoactive medications (61%) and mechanical ventilation (25%). Treatment strategies used included intravenous immunoglobulin (IVIg; 82%), steroids (54%), antiplatelet drugs (64%), and anticoagulation (51%). Mortality for patients with PIMS-TS or MIS-C was low (n = 13). In this systematic review, we highlight key clinical features, laboratory findings, therapeutic strategies, intensive care needs, and observed outcomes for patients with PIMS-TS or MIS-C. Commonly observed clinical manifestations include fever, gastrointestinal symptoms, mucocutaneous findings, cardiac dysfunction, shock, and evidence of hyperinflammation. The majority of children required PICU admission, received immunomodulatory treatment, and had good outcome with low mortality.
Keywords: COVID-19; critically ill children; hyperinflammation; intravenous Immunoglobulin; mechanical ventilation; myocarditis; SARS-CoV-2; steroids